2022
DOI: 10.1021/acs.jafc.2c02692
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Val386 in Transmembrane Domain 8 for the Activation of OATP1B3 by Epigallocatechin Gallate

Abstract: Estrone-3-sulfate (E3S) uptake mediated by organic anion transporting polypeptide 1B3 (OATP1B3) can be activated by epigallocatechin gallate (EGCG). In this study, by using chimeric transporters and site-directed mutagenesis, we found that Val386 in transmembrane domain 8 (TM8) is essential for OATP1B3's activation by EGCG. Kinetic studies showed that the loss of activation of 1B3-TM8 and 1B3-V386F in the presence of EGCG is due to their decreased substrate binding affinity and reduced maximal transport rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Amino acid sequence alignment showed that in both, TM1 and TM8, 5 amino acid residues were different between OATP1B3 and 1B1. , To determine which amino acid residues in TM1 and TM8 are important for the activation of OATP1B3 by clotrimazole, we constructed 5 single mutants for each of TM1 and TM8, by replacing each residue in OATP1B3 with its corresponding residue in OATP1B1. As shown in Figure A, all these 10 mutants had comparable surface expression levels as wild-type OATP1B3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amino acid sequence alignment showed that in both, TM1 and TM8, 5 amino acid residues were different between OATP1B3 and 1B1. , To determine which amino acid residues in TM1 and TM8 are important for the activation of OATP1B3 by clotrimazole, we constructed 5 single mutants for each of TM1 and TM8, by replacing each residue in OATP1B3 with its corresponding residue in OATP1B1. As shown in Figure A, all these 10 mutants had comparable surface expression levels as wild-type OATP1B3.…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies for detecting the six-His tag and the Na + /K + -ATPase α subunit were purchased from Proteintech (66005–1-Ig) and Abcam (ab76020), respectively. Other reagents were obtained from the same companies as previously indicated …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four hours post-transfection, cell surface biotinylation experiment was carried out. The procedures for surface biotinylation and immunoblot analysis were the same as previously described . In brief, plasma membrane proteins were labeled with sulfo- N -hydroxysuccinimide-SS-biotin and isolated with streptavidin–agarose beads after cell lysis.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The procedures for surface biotinylation and immunoblot analysis were the same as previously described. 44 In brief, plasma membrane proteins were labeled with sulfo-N-hydroxysuccinimide-SS-biotin and isolated with streptavidin−agarose beads after cell lysis. Total proteins in cell lysate and isolated membrane proteins were then subjected to immunoblot analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%